Insights into the visitations of oceanic manta rays at cleaning stations on coral reefs in the Bird's Head Seascape, eastern Indonesia - Setyawan, Edy; Mambrasar, Ronald; Sianipar, Abraham B.; Hasan, Abdy W.; Putra, Mochamad I. H.; Mofu, Imanuel; Beale, Calvin S.; Erdmann, Mark V. (Frontiers in Fish Science, 2024)
The globally Endangered oceanic manta ray Mobula birostris is believed to spend significantly more time in the open ocean than in coastal areas. Nonetheless, the Bird’s Head Seascape (BHS) in eastern Indonesia hosts a large population of this species (over 850 individuals), frequently sighted at coral reef cleaning stations and forming a vital asset for marine tourism in the region. Despite this, detailed understanding of the movements and habitat use of this wide-ranging species within shallow (< 30 m) coral reef ecosystems remains limited. Addressing this knowledge gap is urgently required for the sustainable management of oceanic manta ray-focused tourism in the region. Here, we report the results of an initial passive acoustic telemetry study investigating the use of coral reef cleaning stations by oceanic manta rays. Forty-one rays were acoustically tracked from February 2016 to August 2019 in an array of 28 acoustic receivers deployed at known cleaning stations and hypothesized transit points across the BHS (including the regions of Raja Ampat, Fakfak and Kaimana). A total of 5,822 detections were recorded by 16 of the 28 receivers from all tagged individuals, and 421 visitation events were documented from 37 out of the 41 tagged individuals, providing valuable insights into their visitation patterns at cleaning stations. Tagged individuals were detected at receiver stations for durations ranging from 0.2 to 427.0 mins (mean ± SD = 48 ± 64 mins). Notably, 94% of detections were recorded during daylight hours (reaching a peak at noon), underscoring an apparent diurnal pattern in time spent around cleaning stations. The study documented frequent short-range movements between adjacent receivers (5–12 km apart), with two-thirds of all 191 tracked movements occurring between neighboring stations in southern Raja Ampat. Notably, tagged individuals were detected repeatedly at three cleaning stations which were previously only known for hosting reef manta rays, suggesting oceanic manta rays likely also utilize these cleaning stations. Our study provides important insights into the visitations and local movements of oceanic manta rays between coral reef cleaning stations, which will inform effective oceanic manta ray conservation efforts and tourism management in the BHS.